Reynold's model viscosity on radiative MHD flow in a porous medium between two vertical wavy walls - A.B. Disu; M.S. Dada (Journal of Taibah University for Science, 2017)
The two dimensional heat transfer of a free convective–radiative MHD (magnetohydrodynamics) flows with variable viscosity and heat source of a viscous incompressible fluid in a porous medium between two vertical wavy walls was investigated. The fluid viscosity is assumed to vary as an exponential function of temperature. The flow is assumed to consist of a mean part and a perturbed part. The perturbed quantities were expressed in terms of complex exponential series of plane wave equation. The resultant differential equations governing the flow were non-dimensionalised and solved using Differential Transform Method (DTM). The numerical computations were presented in tabular and graphical forms for various fluid parameters. It shows that an increase in radiation, variable viscosity and permeability parameters cause a rise in velocity profile. Nusselt number increases with increase in heat source and decreases with increase in radiation parameter at both walls.